A mutation in X-linked inhibitor of apoptosis (G466X) leads to memory inflation of Epstein–Barr virus-specific T cells. (7th November 2014) - Lopez-Granados, E; Stacey, M; Kienzler, A-K; Sierro, S; Willberg, C B; Fox, C P; Rigaud, S; Long, H M; Hislop, A D; Rickinson, A B; Patel, S; Latour, S; et al.
Summary: Mutations in the X-linked inhibitor of apoptosis (XIAP) gene have been associated with XLP-like disease, including recurrent Epstein–Barr virus (EBV)-related haemophagocytic lymphohystiocytosis (HLH), but the immunopathogenic bases of EBV-related disease in XIAP deficiency is unknown. We present the first analysis of EBV-specific T cell responses in functional XIAP deficiency. In a family of patients with a novel mutation in XIAP (G466X) leading to a late-truncated protein and varying clinical features, we identified gradual hypogammaglobulinaemia and large expansions of T cell subsets, including a prominent CD4 + CD8 + population. Extensive ex-vivo analyses showed that the expanded T cell subsets were dominated by EBV-specific cells with conserved cytotoxic, proliferative and interferon (IFN)-γ secretion capacity. The EBV load in blood fluctuated and was occasionally very high, indicating that the XIAP G466X mutation could impact upon EBV latency. XIAP deficiency may unravel a new immunopathogenic mechanism in EBV-associated disease.